The Meaning of Rationality: A Note on Professor Lange's Article - Rothschild, K. W. (Review of Economic Studies, 1946)
Journal Article The Meaning of Rationality: A Note on Professor Lange's Article Get access K. W. Rothschild K. W. Rothschild Vienna Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 14, Issue 1, 1946, Pages 50–52, https://doi.org/10.2307/2295759 Published: 01 April 1946